Land transfer and green productivity synergies for sustainable agriculture - Fan, Zhiguo; Sun, Cuiping; Zeng, Hongjun; Ma, Shenglin (Journal of Environmental Engineering and Landscape Management, 2026)
The promoting effect of agricultural land circulation on the enhancement of agricultural green total factor productivity (AGTFP) and the high-quality development of China’s agriculture still requires in-depth empirical verification. This study employs the super-efficiency SBM method to quantitatively evaluate AGTFP. Based on panel data from 30 provinces in China spanning the period 2005–2022, it conducts an empirical analysis using fixed-effects models and mediation-effects models. The main research conclusions are as follows: Firstly, the empirical findings indicate that agricultural land circulation has a positive impact on AGTFP, and this conclusion remains robust after undergoing endogeneity tests and robustness checks. Secondly, mechanism analysis reveals that agricultural land circulation effectively elevates the level of AGTFP by promoting economies of scale, accelerating the transfer of rural labor, and facilitating capital deepening, among other pathways (Hu et al., 2025). Meanwhile, economies of scale, labor mobility, and capital deepening also have common and synergistic effects. Thirdly, heterogeneity analysis demonstrates that the enhancing effect of agricultural land circulation on AGTFP is more pronounced in the eastern and central regions, major grain-producing areas, and cultivated regions. Based on the aforementioned research findings, it is recommended that China expedite the reform of its agricultural land circulation system to achieve a steady increase in AGTFP, thereby fostering the development of agriculture.